Industry 4.0 at your home: Printing of hot-working prototypes obtained with low cost fused deposition modeling printers. - Viloria Estrada, Alexander
Additive manufacturing within Industry 4.0 has become a manufacturing trend in multiple areas, in view of its great ease and speed in the manufacture of prototypes or functional parts. The additive manufacturing of metals at a low production cost has become one of the great challenges of the last five years at an industrial and academic level, therefore, the present research work shows the manufacturing route in obtaining metallic components through Extrusion-based additive manufacturing developed by the SENA-UNAL-IMAL consortium for H13 tool steel for hot work application purposes. This research work shows the obtaining of polymer-metal composite materials in filament form to be used in conventional FDM machines, as well as the technical feasibility in terms of printing. Obtained a polymer-metal filament, prototypes of punches for punching were generated. When the prototypes are printed, the process by which the 100% metallic consolidation was achieved through the processes of depolymerization and sintering in solid phase and liquid phase is shown and explained and how these result in changes at the microstructural and mechanical level. The above is currently part of alternative processes to the existing ones that are framed in Industry 4.0 specifically in the area of ​​metal 3D printing.